Grounding Effect on Common Mode Interference of Underground Inverter - CHENG Qiang; CHENG Ning; LI Zhen-shuang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
For the neutral point not grounded characteristics of underground power supply system in coal mine, this paper studied common mode equivalent circuit of underground PWM inverter, and extracted parasitic parameters of interference propagation path. The author established a common mode and differential mode model of underground inverter. Taking into account the rise time of PWM, the simulation results of conducted interference by Matlab software is compared with measurement spectrum on the AC side and motor side of converter, the difference is consistent showing that the proposed method has some validity. After Comparison of calculation results by Matlab simulation ,it can be concluded that ungrounded neutral of transformer could redue common mode current in PWM system, but not very effective, the most efficient way is to increase grounding  impedance of  inverter and motor. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3267